Coordinated Care Organizations: Neonatal and Infant Outcomes in Oregon. (October 2019) - Harvey, S. Marie; Oakley, Lisa P.; Yoon, Jangho; Luck, Jeff
In 2012, Oregon's Medicaid program implemented a comprehensive accountable care model delivered through coordinated care organizations (CCOs). Because CCOs are expected to improve utilization of services and health outcomes, neonatal and infant outcomes may be important indicators of their impact. Estimating difference-in-differences models, we compared prepost CCO changes in outcomes (e.g., low birth weight, abnormal conditions, 5-minute Apgar score, congenital anomalies, and infant mortality) between Medicaid and non-Medicaid births among 99, 924 infants born in Oregon during 2011 and 2013. We further examined differences in the impact of CCOs by ethnicity and rurality. Following CCO implementation the likelihood of low birth weight and abnormal conditions decreased by 0.95% and 1.08%, a reduction of 13.4% and 10.4% compared with the pre-CCO level for Medicaid enrollees, respectively. These reductions could be predictive of lifelong health benefits for infants and lower costs for acute care and are, therefore, important markers of success for the CCO model.